Disinfection of synthetic and real municipal wastewater effluent by flow-through pulsed UV-light treatment system - Uslu, Gulsad; Demirci, Ali; Regan, John M. (Elsevier Science Bv, 2016)
This study was undertaken to characterize the efficacy of flow-through pulsed UV light for inactivation of Escherichia coli and Bacillus subtilis spores in synthetic (SMWE) and real municipal wastewater effluent (RMWE). The results show that complete inactivation was observed with a 10 L/min flow rate for E. coil and 6 L/min flow rate for B. subtilis using one-pass pulsed UV treatment and SMWE. For two-pass treatment, complete inactivation was observed in SMWE with a 16 L/min flow rate for E. coil and 10 L/min flow rate for B. subtilis. On the other hand, complete inactivation was observed with 10 L/min flow rate treatments for E. coil in RMWE, whereas 4.15 Log reduction was observed at 6 L/min for B. subtilis in RMWE for one pass. The raw wastewater was also treated under flow-through pulsed UV light at 10 L/min flow rate and complete inactivation was observed. The treatment resulted in significant chemical oxygen demand (COD) and total organic carbon (TOC) reductions. These results clearly indicate that pulsed UV not only successfully disinfects the wastewater effluent, but also reduces the organic load of municipal wastewater effluent. Therefore, pulsed UV technology can be an alternative for chlorine and conventional UV light for municipal wastewater effluent. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Flow-through; Pulsed UV; Inactivation; Disinfection; Wastewater